First description of the larvae of the fishfly genus Anachauliodes Kimmins, 1954 (Megaloptera: Corydalidae: Chauliodinae) - Tu, Yuezheng; Hayashi, Fumio; Liu, Xingyue (Zootaxa, 2019)
Anachauliodes Kimmins, 1954 (Megaloptera: Corydalidae: Chauliodinae) is a fishfly genus endemic to the Oriental Region with only one recognized species, Anachauliodes laboissierei (Navás, 1913). Currently, the immature stages of this genus are completely unknown. Here we describe the larvae of A. laboissierei for the first time. The larval characters, especially the strongly developed respiratory tubes on the abdominal segment VIII, support a close relationship between Anachauliodes and the eastern Nearctic Chauliodes Latreille, 1796.